The transcription factor FBI‐1 inhibits SAM68‐mediated BCL‐X alternative splicing and apoptosis. (10th February 2014) - Bielli, Pamela; Busà, Roberta; Di Stasi, Savino M; Munoz, Manuel J; Botti, Flavia; Kornblihtt, Alberto R; Sette, Claudio
Synopsis <boxed-text content-type="graphic" id="embr201338241-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> The oncogenic transcription factor FBI‐1 regulates alternative splicing by preventing the splicing regulator SAM68 from binding to BCL‐X mRNA. This increases anti‐apoptotic BCL‐X isoform expression and cell survival. The transcription factor FBI‐1 directly interacts with the splicing regulator SAM68. FBI‐1 impairs binding of SAM68 to BCL‐X mRNA and thus promotes production of the anti‐apoptotic BCL‐X isoform and cell survival. FBI‐1's effect on BCL‐X splicing requires histone deacetylase activity.